2023
DOI: 10.1158/1538-7445.sabcs22-gs4-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS4-02: Oncological Outcomes Following Omission of Axillary Lymph Node Dissection in Node Positive Patients Downstaging To Node Negative with Neoadjuvant Chemotherapy: the OPBC-04/EUBREAST-06/OMA study

Abstract: Background: Data on the oncologic safety of omission of axillary lymph node dissection (ALND) in node positive (N+) patients who downstage to ypN0 with neoadjuvant chemotherapy (NAC) is sparse. Additionally, there is no consensus on which axillary staging procedure should be used in this setting, sentinel lymph node biopsy (SLNB) alone or in combination with localization and retrieval of the clipped positive node, also known as targeted axillary dissection (TAD). Whether the reduction in the false negative rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8]33 These high rates of ax-pCR underline the importance of de-escalating axillary surgery in these patients, as patients with ax-pCR are not expected to benefit from ALND. 36 We found the MLN to be an SN in 72% of the patients. Other studies have shown that the MLN is an SN in 61-96% of the patients.…”
Section: Discussionmentioning
confidence: 69%
“…[1][2][3][4][5][6][7][8]33 These high rates of ax-pCR underline the importance of de-escalating axillary surgery in these patients, as patients with ax-pCR are not expected to benefit from ALND. 36 We found the MLN to be an SN in 72% of the patients. Other studies have shown that the MLN is an SN in 61-96% of the patients.…”
Section: Discussionmentioning
confidence: 69%
“…The omission of SLNB was shown to be non-inferior to sentinel lymph node staging and did not appear to alter adjuvant therapy recommendations. [15] The rationale for this study was the lack of consensus on which axillary staging procedure should be used (targeted axillary dissection [TAD] or dual-tracer SLNB) in nodepositive patients treated with neoadjuvant chemotherapy. The 3-year rate of any axillary recurrence for TAD vs. SLNB was very low (0.5% vs. 0.8%; p = 0.55, respectively), supporting the use of SLNB/TAD alone in node-positive patients after neoadjuvant chemotherapy.…”
Section: Top 5 Papers In Surgicalmentioning
confidence: 99%